Characterization of the PTW SourceCheck ionization chamber with the Valencia lodgment for 125I seed verification. Issue 8 (December 2015) - Tornero-López, Ana M.; Torres del Río, Julia; Ruiz, Carmen; Perez-Calatayud, Jose; Guirado, Damián; Lallena, Antonio M.
Highlights: No additional dependence of air density is required regardless of the number of seeds. The SourceCheck has an asymmetric profile response due to the lodgment. Not considering the profile may lead to too high uncertainties. Abstract: In brachytherapy using 125 I seed implants, a verification of the air kerma strength of the sources used is required. Typically, between 40 and 100 seeds are implanted. Checking all of them is unaffordable, especially when seeds are disposed in sterile cartridges. Recently, a new procedure allowing the accomplishment of the international recommendations has been proposed for the seedSelectron system of Elekta Brachytherapy. In this procedure, the SourceCheck ionization chamber is used with a special lodgment (Valencia lodgment) that allows to measure up to 10 seeds simultaneously. In this work we analyze this procedure, showing the feasibility of the approximations required for its application, as well as the effect of the additional dependence with the air density that shows the chamber model used. Uncertainty calculations and the verification of the approximation needed to obtain a calibration factor for the Valencia lodgment are carried out. The results of the present work show that the chamber dependence with the air density is the same whether the Valencia lodgment is used or not. On the contrary, the chamber response profile is influenced by the presence of the lodgment. The determination of this profile requires various measurements due to the nonnegligible variability found between different experiments. If it is considered, the uncertainty in the determination of the air-kerma strength increases from 0.5% to 1%. Otherwise, a systematic additional uncertainty of 1% would occur. This could be relevant for the comparison between user and manufacturer measurements that is mandatory in the case studied here.